Penyuluhan Untuk Meningkatkan Membaca Al-Qur’an Dengan Baik dan Benar Yang Sesuai Dengan Kaidah-Kaidah Ilmu Tajwid Di TPQ Baytul Munir Dusun Krajan Desa Besowo - Maimun Aziz Ismail; Muhammad As’adur Rofik (LP3M IAIFA Kediri, 2023)
EdEducation is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, the nation's community and the state of the Qur'an. An''an is a way of life for Muslims in this life and especially in the hereafter. In this study, the author uses a research approach called PAR (Participatory Action Research). The data sources in this study were all activities in the Krajan Besowo settlement, especially children's activities and daily activities. The Rules of Tajwid Science at TPQ Baytul Munir, Dusun Krajan, Besowo Village” on July 25, 2022 – August 24, 2022 in Dusun Krajan, Besowo Village, Kepung District, Kediri Regency brought a few significant changes. The application of this counseling method is effective in educating children to be more active in learning and understanding problems related to reading the Qur'an properly and correctly in accordance with the rules of tajwid science because individual teaching and learning activities can increase the activity of children so that they can read the Qur'an well and true, with the application of this method will lead to a diverse learning process.